Identification of 4‐hydroxynonenal protein targets in rat, mouse and human liver microsomes by two‐dimensional liquid chromatography/tandem mass spectrometry. (7th June 2016) - Golizeh, Makan; Geib, Timon; Sleno, Lekha
Abstract : Rationale: 4‐Hydroxynonenal (HNE), endogenously generated through peroxidation and breakdown of polyunsaturated fatty acids, has been linked to a number of adverse biological effects through carbonylation of essential biomolecules. Covalent binding of HNE to proteins can alter their structure and functions, causing cell damage as well as adverse immune responses. The liver plays a predominant role in metabolic transformations and hepatic proteins are often targeted by reactive metabolites. Methods: Rat, mouse and human liver microsomes were incubated with HNE, enzymatically digested, and subjected to strong cation‐exchange peptide fractionation prior to liquid chromatography/tandem mass spectrometry (LC/MS/MS) analysis coupled to electrospray ionization quadrupole time‐of‐flight (QqTOF) mass spectrometry. HNE‐modified peptides were detected by probability‐driven peptide spectral matching and comparative analysis between treated and control samples, and confirmed based on accurate mass and high‐resolution MS/MS spectra. Results: A total of 99, 123 and 51 HNE‐modified peptides were identified in rat, mouse and human liver microsomes related to 76, 103 and 44 target proteins, respectively. Eight proteins were found to be adducted by HNE in all three species, including ATP synthase, carbamoyl phosphate synthase, cytochrome P450 1A2, glutamate dehydrogenase 1, protein ERGIC‐53, protein disulfide‐isomerase, and voltage‐dependent anion‐selective channel protein 1. These proteins play crucial roles in cellular processes and their covalent modification could potentially alter their function and lead to cytotoxicity. Conclusions: An analytical approach was developed for the identification of in vitro HNE protein targets in rat, mouse and human liver microsomes using two‐dimensional (2D) LC/MS/MS. This approach can be applied to study HNE modification of proteins in vitro and in vivo, providing insight into the toxicology of HNE protein adduction. Copyright © 2016 John Wiley & Sons, Ltd.